Tree diversity depending on environmental gradients promotes biomass stability via species asynchrony in China's forest ecosystems. (July 2022) - Wu, Anchi; Zhou, Guoyi; He, Honglin; Hautier, Yann; Tang, Xuli; Liu, Juxiu; Zhang, Qianmei; Wang, Silong; Wang, Anzhi; Lin, Luxiang; Zhang, Yiping; Xie, Zongqiang; et al.
Highlights: Species richness indirectly increases temporal biomass stability by promoting species asynchrony, rather than through a direct influence. Forest age and structural diversity increased temporal mean biomass and biomass variability significantly and simultaneously. Soil nitrogen enhanced biomass stability directly and indirectly through its effects on mean biomass. The direct and indirect effects of soil properties on temporal biomass stability were greater than that of climate variables. Abstract: There is mounting evidence that biodiversity promotes ecological stability in changing environments. However, understanding diversity–stability relationships and their underlying mechanisms across large-scale tree diversity and natural environmental gradients are still controversial and largely lacking. We used thirty-nine 0.12 ha long-term permanent forest plots spanning China's various forest types to test the effects of multiple abiotic (climate, soil, age and topography) and biotic factors (taxonomic and structural diversity, functional diversity and community-mean traits, and species asynchrony) on biomass stability and its components (mean biomass and biomass variability) over time. We used multiple analytical methods to identify the best explanatory variables and complicated causal relationships for community biomass stability. Our results showed that species richness increased biomass stability by promoting species asynchrony. Structural and functional diversity had a weaker effect on biomass stability. Forest age and structural diversity increased mean biomass and biomass variability significantly and simultaneously. Communities dominated by tree species with high wood density had high biomass stability. Soil nitrogen enhanced biomass stability directly and indirectly through its effects on mean biomass. Soil nitrogen to phosphorus ratio increased biomass stability via increasing species asynchrony. Precipitation indirectly increased biomass stability by affecting tree diversity. Moreover, the direct and indirect effects of soil nutrients on biomass stability were greater than that of climate variables. Our results suggest that species asynchrony is the main mechanism proposed to explain the stabilizing effect of diversity on community biomass, supporting two mechanisms, namely, the biodiversity insurance hypothesis and complementary dynamics. Soil and climate factors also play an important role in shaping diversity–stability relationships. Our results provide a new insight into how tree diversity affects ecosystem stability across diverse community types and large-scale environmental gradients.